Momentary experiential avoidance: Within-person correlates, antecedents, and consequences and between-person moderators. (August 2018) - Wenze, Susan J.; Gaugler, Trent L.; Sheets, Erin S.; DeCicco, Jennifer M.
Abstract: We used ecological momentary assessment to investigate momentary correlates, antecedents, and consequences of experiential avoidance (EA), and to explore whether depression and anxiety moderate these within-person relationships. Participants recorded their mood, thoughts, stress, and EA four times daily for one week. Baseline depression and anxiety were associated with EA. EA was lower when participants reported more positive mood and thoughts, and higher when participants reported more negative mood, negative thoughts, and stress. The EA-stress relationship was stronger for participants with higher depression. Lag analyses showed that negative mood, negative thoughts, and stress predicted subsequent EA. In turn, EA predicted subsequent negative mood, negative thoughts, and stress. The relationship between EA and subsequent negative thoughts was stronger for participants with higher anxiety. Participants with higher depression and anxiety had a less negative association between positive thoughts and subsequent EA. This study adds to a growing body of literature on the process of EA as it unfolds in vivo, in real-time. Findings highlight links between momentary negative internal experiences and EA (which may be especially strong for people with depression or anxiety) and suggest that certain positive subjective experiences may buffer against EA. Clinical implications and future research directions are discussed. Highlights: EA lower with positive mood/thoughts, higher with negative mood/thoughts, stress. EA-stress relationship moderated by depression. Negative mood/thoughts & stress precede EA, which precedes negative mood/thoughts & stress. Lagged EA-negative thoughts relationship moderated by anxiety. Lagged positive thoughts-EA relationship moderated by depression and anxiety.